2020
DOI: 10.3390/plants9050659
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Clean Label Fish Patty with Olive, Citric, Pomegranate, or Rosemary Extracts

Abstract: The natural functional ingredients derived from pomegranate (41.4% punicalagin), rosemary (5.8% carnosic acid and carnosol), hydroxytyrosol (7.3%), and citrus (55% hesperidin) fruits were combined separately with acerola (17% vitamin C) and essential oils rich in fatty acids (45% α-linolenic (ALA) and 40% docosahexaenoic (DHA)) provide a natural substitute of synthetic preservatives for fish patties, avoiding E-numbers on labels. Microbiological and physicochemical properties of the formulations were examined,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 58 publications
2
11
0
Order By: Relevance
“…A similar result was reported by Martinez‐Zamora et al. (2020), who found that fish patties treated with rosemary extract had ameliorated organoleptic characteristics and reduced TMA content.…”
Section: Resultssupporting
confidence: 89%
“…A similar result was reported by Martinez‐Zamora et al. (2020), who found that fish patties treated with rosemary extract had ameliorated organoleptic characteristics and reduced TMA content.…”
Section: Resultssupporting
confidence: 89%
“…For instance, Azaizeh et al [ 34 ] showed as 400 μg/mL HT extract inhibited by 100% the growth of Streptococcus pyogenes, Staphylococcus aureus, Escherichia coli, and Klebsiella pneumoniae . In fact, this behavior has been also reported as food preservative in chicken nuggets for twelve months of frozen storage [ 17 ] and fish patties for eleven days of refrigerated storage [ 32 , 35 ] applied at 750 and 200 ppm, respectively.…”
Section: Discussionmentioning
confidence: 89%
“…Obtained results can be supported by the rest of the assessed characteristics where the antioxidant and antimicrobial capacities of HT were demonstrated ( Figure 1 , Table 5 and Table 6 ). Additionally, the antioxidant activity of HT has been repeatedly demonstrated by several authors, as in vitro [ 36 , 37 , 38 ], as in vivo [ 39 , 40 , 41 , 42 , 43 , 44 ] or as a preserver in a food matrix [ 17 , 30 , 31 , 32 , 35 , 45 , 46 , 47 ]. For that, incorporation of this kind of products in a balanced Mediterranean Diet could report significant health benefits of consumers in comparison with usual manufactured meat products rich in synthetic additives.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst natural preservatives, rosemary, thyme, and basil have been widely applied and reported for their preservation abilities due to antioxidant and antimicrobial activity as well as higher total phenolic content [ 14 , 17 ]. Additionally, they have improved the sensory and nutritional qualities in fishery products [ 15 , 16 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%